Tafsir As Social Criticism: The Case of Tafsir Malja’ Al Thalibin and Tamsiyyat Al Muslimin by KH Ahmad Sanusi - Lutfi, Lutfi (Islamic Religious Education Departement, 2024)
This research examines two seminal works of Ahmad Sanusi, Malja’ al Ta>libin fi> tafsi>ri kala>mi robb al ‘a>lamin (in Sundanese) and Tamsiyat al muslimi>n fi> tafsi>ri kala>mi robb al ‘a>lami>n (in Indonesian Bahasa). By understanding Sanusi's interpretation and context of the production of the text, this research shows that Sanusi used his interpretation as a medium to criticize colonial government policies and emphasize the importance of education, especially mastering secular knowledge, besides the religious one to achieve Indonesian glory and independence. This research explores Sanusi’s anti-colonial criticism of the Teacher Ordinance Act, the prohibition of learning in pesantren and performing hajj. Furthermore, Sanusi encourages people to master secular sciences besides religious ones to achieve Indonesian independence. This research employs Hermeneutics to analyze Sanusi’s two books of tafsir. This method provides an understanding of the social, political, and cultural context of the production of the text.",